Carbon-based hierarchical scaffolds for myoblast differentiation: Synergy between nano-functionalization and alignment. (1st March 2016) - Patel, Akhil; Mukundan, Shilpaa; Wang, Wenhu; Karumuri, Anil; Sant, Vinayak; Mukhopadhyay, Sharmila M.; Sant, Shilpa
Graphical abstract: Abstract: While several scaffolds have been proposed for skeletal muscle regeneration, multiscale hierarchical scaffolds with the complexity of extracellular matrix (ECM) haven't been engineered successfully. By precise control over nano- and microscale features, comprehensive understanding of the effect of multiple factors on skeletal muscle regeneration can be derived. In this study, we engineered carbon-based scaffolds with hierarchical nano- and microscale architecture with controlled physico-chemical properties. More specifically, we built multiscale hierarchy by growing carbon nanotube (CNT) carpets on two types of scaffolds, namely, interconnected microporous carbon foams and aligned carbon fiber mats. Nanostructured CNT carpets offered fine control over nano-roughness and wettability facilitating myoblast adhesion, growth and differentiation into myocytes. However, microporous foam architecture failed to promote their fusion into multinucleated myotubes. On the other hand, aligned fibrous architecture stimulated formation of multinucleated myotubes. Most importantly, nanostructured CNT carpets interfaced with microscale aligned fibrous architecture significantly enhanced myocyte fusion into multinucleated mature myotubes highlighting synergy between nanoscale surface features and micro-/macroscale aligned fibrous architecture in the process of myogenesis. Statement of Significance: Due to limited regenerative potential of skeletal muscle, strategies stimulating regeneration of functional muscles are important. These strategies are aimed at promoting differentiation of progenitor cells (myoblasts) into multinucleated myotubes, a key initial step in functional muscle regeneration. Recent tissue engineering approaches utilize various scaffolds ranging from decellularized matrices to aligned biomaterial scaffolds. Although, majority of them have focused on nano- or microscale organization, a systematic approach to build the multiscale hierarchy into these scaffolds is lacking. Here, we engineered multiscale hierarchy into carbon-based materials and demonstrated that the nanoscale features govern the differentiation of individual myoblasts into myocytes whereas microscale alignment cues orchestrate fusion of multiple myocytes into multinucleated myotubes underlining the importance of multiscale hierarchy in enhancing coordinated tissue regeneration.